2010
DOI: 10.1002/we.393
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the casting process of a wind turbine rotor hub

Abstract: An integrated numerical model was applied to simulate the mold filling and solidification process as well as predict the occurrence of relative casting defects for a rotor hub casting. The goal was to conduct a numerical experimentation to obtain an optimal alloy design of ductile cast iron for the rotor hub casting. A computer‐aided engineering software based on the finite element method was employed in this study. Numerical simulations were conducted for the rotor hub casting with two different types of allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The simulation results showed that particle clustering/ accumulation was caused by particle pushing, and the particles were distributed more uniformly as the pouring temperature increased. Yeh et al [7] performed a numerical simulation of the mold filling and solidification processes and predicted the occurrence of relative casting defects in rotor hub casting using an integrated numerical model. Then, to alleviate the casting defects in the rotor hub casting, a better alloy design was proposed based on the simulated results to alleviate casting defects of the rotor hub casting.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that particle clustering/ accumulation was caused by particle pushing, and the particles were distributed more uniformly as the pouring temperature increased. Yeh et al [7] performed a numerical simulation of the mold filling and solidification processes and predicted the occurrence of relative casting defects in rotor hub casting using an integrated numerical model. Then, to alleviate the casting defects in the rotor hub casting, a better alloy design was proposed based on the simulated results to alleviate casting defects of the rotor hub casting.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of infrastructure construction, the demand for ductile iron parts in wind power, high-speed railways, engineering machinery and other industries has gradually increased. These castings work in the harsh environment and require high comprehensive performance of ductile iron, which requires high strength and good plasticity [8,9]. Therefore, improving the tensile strength, yield strength, hardness and elongation of ductile iron at room temperature is of great significance to engineering practice.…”
Section: Introductionmentioning
confidence: 99%